Reconstruction of the Guarantee's Objects in the Fiduciary Agreement in Indonesia - Supriyadi, Supriyadi (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Normally, the laws and fiduciary agreements made by the parties also affect the lex specialis, therefore, it is necessary to carry out the reconstruction of the fiduciary law. This research was a descriptive study that was analyzed qualitatively from secondary data. The approach used was the normative legal approach. The problem that often arises in the fiduciary law is with respect to the position of the fiduciary security object. Problems arise when fiduciary recipients execute collateral objects obstructed by the donor that has been transferred to a third party.